THE EFFECT OF DATA DRIVEN LEARNING TO IMPROVE VOCABULARY IN THE SECOND YEAR OF UNIVERSITY STUDENTS - Asti Ramadhani Endah Lestari (UICELL, 2022)
The goal of the present study is to compare the effectiveness of using the Data-Driven Learning approach and the traditional method of teaching vocabulary like a consultation with a grammar book and a lecturer’s presentation. Two intact classes (N = 37) and (N = 38) taking Vocabulary subjects comprised the experimental and control groups, respectively. The researcher administered Nation’s standardized vocabulary size test as a pre-test to ensure that the participants were at the same level of vocabulary knowledge. During the semester, the experimental group was taught using COCA. The finding showed that the experimental group exhibited a significantly marked increase in vocabulary results after the experiment. In General, the study revealed that DDL has a beneficial side-effect in improving university students’ vocabularies as it enables students to perform an active role in the learning process. Keywords: Data-driven learning, vocabulary